An investigation on the precipitated phases and mechanical properties of cerium modified 2024 aluminum alloy. Issue 9 (18th September 2020) - Xia, Y.; Wang, D.; Jia, J.; Wu, J.; Wang, Z.; Li, X.; Yuan, W.; Huang, J.
Abstract: The effects of the addition of rare earth cerium on the cast microstructure and mechanical properties of 2024‐T6 aluminum alloy were investigated in this work. The specimens for room‐temperature tensile tests were prepared with a T6 heat treatment. Experimental results indicated that the cerium modified alloys showed refined grains, higher hardness, and strength values at room temperature. The hardness and the strength of the cerium modified alloys initially increased and then decreased as the cerium content increased. The maximum tensile strength was obtained at the 0.6 wt.% cerium modified 2024 aluminum alloy. This was improved from 464 MPa to 612 MPa. Simultaneous increases in the tensile strength and hardness were proposed to result from the refined α‐aluminum dendrites, the formation of aluminum‐rare earth intermetallic compounds at the grain boundaries and the grains, the more homogeneously distributed nano‐scale S precipitates, and the smaller T diffusion phase. Abstract : According to this paper, the strength of the cerium modified 2024 aluminum alloys initially increased and then decreased as the cerium content increased. The maximum tensile strength was obtained at the 0.6 wt.% cerium modified 2024 aluminum alloy. Simultaneous increases in the tensile strength and hardness were proposed to result from the refined α‐aluminum dendrites, the formation of aluminum‐rare earth intermetallic compounds at the grain boundaries and the grains, the more homogeneously distributed nano‐scale S precipitates, and the smaller T diffusion phase.